POLA ASUH ORANG TUA TERHADAP ANAK PADA KELUARGA NELAYAN TRADISIONAL PANCING ULUR DI DESA BORGO KECAMATAN TOMBARIRI KABUPATEN MINAHASA - Keith Imanuel Kandey; Djuwita R.R. Aling; Grace O. Tambani; Swenekhe S. Durand; Christian R. Dien; Steelma V. Rantung (Universitas Sam Ratulangi, 2023)
Abstract This study aims to determine the general condition of traditional fishermen families in Borgo Village, Tombariri Subdistrict, Minahasa Regency, and also to determine the parenting patterns of parents towards children in traditional fishermen families in Borgo Village, Tombariri Subdistrict, Minahasa Regency. The method used in this research is a case study. A case study is an exploration of a bounded system or a case or various case over time through data collection and involving various rich sources of information in a context. The population in this study was 136 traditional fishing families in Borgo Village. Data were collected using purposive sampling technique. The sample taken was 15 fishermen families (11% of the total population) who had children. Primary data collection used observation, interviews and questionnaires, while secondary data were obtained from statistical records available at government institutions in Borgo Village Office. The data analysis used was descriptive qualitative and descriptive quantitative analysis, using the Guttman scale, which is research that when you want to get a firm answer to a stated problem and is always made in the choice of